Multilayer structure, vacuum packaging bag and vacuum insulator

A multilayer structure with a biaxially stretched polyvinyl alcohol resin film and modified polyvinyl alcohol overcoat layer maintains high barrier properties under stress, addressing the issue of conventional films deteriorating under bending or stretching.

JP7610514B2Active Publication Date: 2025-01-08KURARAY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021542847
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-23
Filing Date
2020-08-21
Publication Date
2025-01-08
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

Conventional gas barrier films used in vacuum insulation deteriorate when subjected to physical stress such as bending or stretching, compromising their barrier properties.

Method used

A multilayer structure comprising a biaxially stretched polyvinyl alcohol resin film as the base material, an inorganic vapor-deposited layer, and an overcoat layer made of modified polyvinyl alcohol with specific thickness and polar group content, ensuring high barrier properties even under stress.

Benefits of technology

The multilayer structure maintains excellent gas barrier properties even when subjected to bending, enhancing the durability and performance of vacuum packaging bags and insulation bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610514000004
    Figure 0007610514000004
  • Figure 0007610514000001
    Figure 0007610514000001
  • Figure 0007610514000002
    Figure 0007610514000002
Patent Text Reader

Abstract

A multilayered structure provided, in this order, with a substrate (X), an inorganic vapor deposition layer (Y) and an overcoat layer (Z), wherein: the substrate (X) comprises a biaxially oriented polyvinyl alcohol resin film; the overcoat layer (Z) contains a modified polyvinyl alcohol (A) which has a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the vinyl alcohol unit (a); and the thickness of the overcoat layer (Z) is 0.003-5μm, inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-layer structure, a vacuum packaging bag, and a vacuum insulator. [Background technology]

[0002] Conventionally, polyurethane foam has been widely used as an insulator for refrigerators, residential insulating walls, storage tanks, etc. In recent years, vacuum insulators have been used as an alternative insulator. Vacuum insulators make it possible to achieve the same insulating properties as those of insulators made of polyurethane foam, but in a thinner and lighter form. Vacuum insulators are expanding their applications and demand as insulators used to insulate heat transfer equipment such as heat pump application equipment, heat storage equipment, living spaces, vehicle interior spaces, etc.

[0003] An example of a vacuum insulator is one that includes a vacuum packaging bag and a core material disposed inside the vacuum packaging bag, and one of the properties required for a vacuum packaging bag is barrier properties. For this reason, vacuum packaging bags with improved barrier properties and barrier films for use therein have been proposed.

[0004] For example, Patent Document 1 describes a gas barrier film having a vapor-deposited film on one side of an ethylene-vinyl alcohol copolymer film and a coating layer of polyvinyl alcohol containing an inorganic substance adjacent to the vapor-deposited film, as a film used for a vacuum packaging bag with enhanced gas barrier properties. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-114520 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the above-mentioned conventional gas barrier films may suffer from reduced barrier properties when subjected to physical stresses such as stretching and bending during the manufacturing process of vacuum insulators or the like.

[0007] An object of the present invention is to provide a multilayer structure, a vacuum packaging bag, and a vacuum insulator that can maintain high barrier properties even when subjected to physical stress such as bending. [Means for solving the problem]

[0008] That is, the present invention [1] A multilayer structure comprising a substrate (X), an inorganic vapor deposition layer (Y) and an overcoat layer (Z) in this order, in which the substrate (X) is made of a biaxially stretched polyvinyl alcohol-based resin film, the overcoat layer (Z) contains a modified polyvinyl alcohol (A) having a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the vinyl alcohol unit (a), and the thickness of the overcoat layer (Z) is 0.003 μm or more and 5 μm or less; [2] The multilayer structure of [1], in which the proportion of the monomer units (b) having a polar group in all monomer units constituting the modified polyvinyl alcohol (A) is 0.05 mol % or more and 30 mol % or less; [3] The multilayer structure according to [1] or [2], wherein the polar group is at least one selected from the group consisting of a carboxy group, an ester group, and a silanol group; [4] The maximum intensity ratio (I(B) / I(C)) obtained by the following steps (1) to (3) MAX ) is 1.20 or more; (1) At five arbitrarily selected points on the surface of the overcoat layer (Z), a depth direction analysis is performed by TOF-SIMS. (2) For each detected fragment, calculate the average maximum fragment intensity at each measurement point (I(B)), and the average intensity at the midpoint between the measurement start point and the measurement point of maximum intensity at each measurement point (I(C)). The ratio of these is the intensity ratio (I(B) / I(C)). (3) The maximum intensity ratio (I(B) / I(C)) of each fragment is calculated. MAX ) [5] The multilayer structure according to any one of [1] to [4], further comprising a layer (J) other than the substrate (X), the inorganic vapor deposition layer (Y), and the overcoat layer (Z); [6] The multilayer structure according to [5], comprising at least two other layers (J), and comprising a substrate (X), an inorganic vapor deposition layer (Y), and an overcoat layer (Z) between the at least two other layers (J); [7] The multilayer structure of any one of [1] to [6], wherein the biaxially stretched polyvinyl alcohol-based resin film is a biaxially stretched film containing as a main component an ethylene-vinyl alcohol copolymer having an ethylene unit content of 10 mol% or more and 65 mol% or less and a saponification degree of 90 mol% or more; [8] In the Gelboflex test according to ASTM F 392, after three repeated reciprocating movements, the oxygen permeability measured according to JIS K7126 under conditions of 40°C, 0% RH (carrier gas side), and 90% RH (oxygen supply side) was 2.0 ml / (m 2 A multilayer structure of any one of [1] to [7], in which the thermal conductivity is less than 100% (day·atm); [9] A vacuum packaging bag comprising any one of the multilayer structures of [1] to [8];

[10] [9] A vacuum insulator comprising a vacuum packaging bag and a core material disposed inside the vacuum packaging bag, the inside of which is reduced in pressure; This is achieved by providing Effect of the Invention

[0009] According to the present invention, it is possible to provide a multilayer structure, a vacuum packaging bag, and a vacuum insulator that can maintain high barrier properties even when subjected to physical stress such as bending. [Brief description of the drawings]

[0010] [Figure 1] 13 is a graph showing one of the measurement results of SiO2 in the depth direction analysis using TOF-SIMS in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In this specification, unless otherwise specified, "gas barrier properties" refers to the ability to barrier gases other than water vapor. In addition, in this specification, when simply described as "barrier properties", it refers to both gas barrier properties and water vapor barrier properties. In addition, the property of "being able to maintain high barrier properties even when subjected to physical stress such as bending" is sometimes expressed as "flex resistance".

[0012] (Multilayer structure) The multilayer structure of the present invention comprises a substrate (X), an inorganic vapor deposition layer (Y) and an overcoat layer (Z) in this order, the substrate (X) being a biaxially stretched polyvinyl alcohol-based resin film (hereinafter sometimes abbreviated as "biaxially stretched PVA-based resin film"), the overcoat layer (Z) containing a modified polyvinyl alcohol (A) (hereinafter sometimes abbreviated as "modified PVA (A)") having a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the vinyl alcohol unit (a), and the thickness of the overcoat layer (Z) is 0.003 μm or more and 5 μm or less. The multilayer structure of the present invention tends to exhibit good bending resistance by comprising an inorganic vapor deposition layer (Y) on the substrate (X) and a specific thickness of the overcoat layer (Z) containing the modified PVA (A). In the multilayer structure, the substrate (X) and the inorganic vapor deposition layer (Y) may be in direct contact with each other, or another layer may be interposed. Similarly, the inorganic vapor deposition layer (Y) and the overcoat layer (Z) may be in direct contact with each other or may have another layer interposed therebetween, but it is preferable that the inorganic vapor deposition layer (Y) and the overcoat layer (Z) are in direct contact with each other. In the multilayer structure, the inorganic vapor deposition layer (Y) and the overcoat layer (Z) may be provided on both sides of the substrate (X).

[0013] (Base material (X)) The multilayer structure of the present invention exhibits excellent gas barrier properties due to the substrate (X) made of a biaxially stretched PVA-based resin film. In addition, the substrate (X) is made of a biaxially stretched PVA-based resin film, which enhances the affinity with the inorganic vapor deposition layer (Y) described below and improves the flex resistance.

[0014] The biaxially stretched PVA resin film is a biaxially stretched film containing a PVA resin as a main component. The main component refers to the component with the largest content by mass. The content of the PVA resin in the substrate (X), i.e., the biaxially stretched PVA resin film, is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 99% by mass or more.

[0015] The PVA-based resin may be any resin having a vinyl alcohol unit formed by saponifying a vinyl ester unit, and examples thereof include polyvinyl alcohol (hereinafter sometimes abbreviated as "PVA") resin and ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as "EVOH") resin. Among them, EVOH resin is preferred as the PVA-based resin from the viewpoint of obtaining a multilayer structure having excellent flex resistance. That is, the substrate (X) is preferably made of a biaxially stretched EVOH resin film.

[0016] Examples of PVA resins include PVA resins obtained by homopolymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate, followed by saponification. The PVA resin in the present invention may be a modified PVA resin that has been copolymerized or post-modified. The homopolymerization of vinyl esters and the saponification of vinyl ester homopolymers can be carried out by known methods. The copolymerized modified PVA resin is produced by copolymerizing, for example, the above-mentioned vinyl ester with an unsaturated monomer copolymerizable with the vinyl ester, followed by saponification, and the degree of modification is usually less than 10 mol%.

[0017] Examples of unsaturated monomers copolymerizable with vinyl esters include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 4-penten-1-ol, and 5-hexen-1-ol, as well as derivatives thereof such as acylated products; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid, as well as their salts, monoesters, and dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; diacetone acrylamide, acrylic amides such as amide and methacrylamide; olefin sulfonic acids or salts thereof such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; vinyl compounds such as alkyl vinyl ethers, dimethyl allyl vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxolane, glycerin monoallyl ether, and 3,4-diacetoxy-1-butene; substituted vinyl acetates such as isopropenyl acetate and 1-methoxyvinyl acetate; vinylidene chloride, 1,4-diacetoxy-2-butene, and vinylene carbonate.

[0018] The post-modified PVA resin can be obtained by post-modifying PVA by a method such as acetoacetate esterification, acetalization, urethanization, etherification, grafting, phosphate esterification, or oxyalkylenation.

[0019] In the present invention, the viscosity average degree of polymerization of the PVA resin is preferably 1100 or more, more preferably 1200 or more. The viscosity average degree of polymerization of the PVA resin is preferably 4000 or less, more preferably 2600 or less. When the viscosity average degree of polymerization of the PVA resin is 1100 or more, it is preferable because the mechanical strength of the resulting vacuum packaging bag is good. On the other hand, when the viscosity average degree of polymerization is 4000 or less, it is preferable because the processability during film formation and stretching is good. The saponification degree of the PVA resin is preferably 90 mol% or more, more preferably 95 mol% or more, and even more preferably 99 mol% or more. The saponification degree of the PVA resin may be 100 mol% or less or 99.9 mol% or less. When the saponification degree is within the above range, it is preferable because the water resistance is improved and the gas barrier property against humidity is good. The viscosity average degree of polymerization and the saponification degree of the PVA resin can be measured according to the method described in JIS K 6726 (1994).

[0020] EVOH resins are usually obtained by saponifying a copolymer of ethylene and a vinyl ester such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate. The production and saponification of the copolymer of ethylene and a vinyl ester can be carried out by a known method. The saponification degree of the vinyl ester component of the EVOH resin is preferably 90 mol % or more, more preferably 95 mol % or more, and even more preferably 99 mol % or more. By making the saponification degree 90 mol % or more, the gas barrier property can be improved. The saponification degree of the EVOH resin may be 100 mol % or less, or may be 99.99 mol % or less. The saponification degree of the EVOH resin can be measured by nuclear magnetic resonance ( 1 H-NMR measurement is performed to measure the peak area of ​​hydrogen atoms contained in the vinyl ester structure and the peak area of ​​hydrogen atoms contained in the vinyl alcohol structure.

[0021] The ethylene unit content of the EVOH resin is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, and even more preferably 25 mol% or more. The ethylene unit content of the EVOH resin is preferably 65 mol% or less, more preferably 55 mol% or less, and even more preferably 50 mol% or less. When the ethylene unit content is 10 mol% or more, the gas barrier property and flex resistance under high humidity tend to be maintained well. On the other hand, when the ethylene unit content is 65 mol% or less, the gas barrier property can be improved. The ethylene unit content of the EVOH resin can be determined by NMR method.

[0022] In addition, the EVOH resin may have units derived from other monomers other than ethylene, vinyl esters, and saponified products thereof, within the scope of not impairing the object of the present invention. When the EVOH resin has the other monomer units, the content of the other monomer units relative to the total monomer units of the EVOH resin is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, and particularly preferably 5 mol% or less. When the EVOH resin has the units derived from the other monomers, the lower limit may be 0.05 mol% or 0.10 mol%. Examples of the other monomers include alkenes such as propylene, butylene, pentene, and hexene; 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, and 4-acyloxy-3-methyl. -1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, 5,6-diacyloxy-1-hexene, 1,3-diacetoxy-2-methyl alkenes having an ester group such as dimethylpropane or saponified products thereof; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, or the like, or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, methallylsulfonic acid, or the like, or their salts; vinyl silane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxy-ethoxy)silane, γ-methacryloxypropylmethoxysilane; alkyl vinyl ethers, vinyl ketones, N-vinylpyrrolidone, vinyl chloride, vinylidene chloride, and the like.

[0023] In addition, when the EVOH resin is a blend of two or more different EVOH resins, the average ethylene unit content or saponification degree of the entire EVOH resin is regarded as the ethylene unit content or saponification degree of the EVOH resin.

[0024] The biaxially stretched PVA-based resin film may contain other components, such as, for example, a carboxylic acid compound, a phosphoric acid compound, a boron compound, a metal salt, a stabilizer, an antioxidant, an ultraviolet absorber, an antistatic agent, a lubricant, a colorant, a filler, a desiccant, and a reinforcing agent such as various fibers, as long as the effects of the present invention are not impaired.

[0025] A film formed using a PVA resin is used as the substrate (X). A known method can be used for forming such a film, for example, a casting method in which a solution of a PVA resin is cast onto a metal surface such as a drum or an endless belt to form a film, or a melt molding method in which the resin is melt-extruded by an extruder, etc. can be used.

[0026] Such a PVA-based resin film is used after being biaxially stretched according to a known method such as simultaneous biaxial stretching or sequential biaxial stretching. From the viewpoints of thickness uniformity, barrier properties, mechanical properties, and film formability, the stretching ratio is preferably in the range of 2.5 to 4.5 times in the longitudinal direction (MD direction), 2.5 to 4.5 times in the transverse direction (TD direction), and 7 to 15 times as the areal stretching ratio, and more preferably in the range of 2.5 to 3.5 times in the longitudinal direction, 2.5 to 3.5 times in the transverse direction, and 8 to 12 times as the areal stretching ratio. If the PVA-based resin film is not biaxially stretched, bending resistance and gas barrier properties may be reduced.

[0027] The thickness of the substrate (X) is not particularly limited, but from the viewpoint of industrial productivity, it is preferably 5 μm or more, more preferably 8 μm or more, and even more preferably 10 μm or more. The thickness of the substrate (X) is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 40 μm or less, and particularly preferably 30 μm or less. The thickness is the average value of values ​​measured at any five points. The same applies to other thicknesses below.

[0028] (Inorganic vapor deposited layer (Y)) The inorganic vapor deposition layer (Y) is usually a layer having a barrier property against oxygen and water vapor, and can be formed by vapor deposition of an inorganic material. Examples of inorganic materials include metals (e.g., aluminum), metal oxides (e.g., silicon oxide, aluminum oxide), metal nitrides (e.g., silicon nitride), metal nitride oxides (e.g., silicon oxynitride), and metal carbonitrides (e.g., silicon carbonitride). Among them, aluminum, aluminum oxide, silicon oxide, magnesium oxide, and silicon nitride are preferred from the viewpoint of excellent barrier properties after bending, and aluminum is more preferred.

[0029] The method for forming the inorganic vapor deposition layer (Y) is not particularly limited, and examples thereof include physical vapor deposition methods such as vacuum deposition (e.g., resistance heating deposition, electron beam deposition, molecular beam epitaxy, etc.), sputtering, and ion plating; and chemical vapor deposition methods such as thermal chemical vapor deposition (e.g., catalytic chemical vapor deposition), photochemical vapor deposition, plasma chemical vapor deposition (e.g., capacitively coupled plasma, inductively coupled plasma, surface wave plasma, electron cyclotron resonance, dual magnetron, atomic layer deposition, etc.), and metalorganic chemical vapor deposition.

[0030] The thickness of the inorganic vapor deposition layer (Y) varies depending on the type of components constituting the inorganic vapor deposition layer (Y), but is preferably 0.002 μm to 0.5 μm, more preferably 0.005 μm to 0.2 μm, and even more preferably 0.01 μm to 0.1 μm. When the inorganic vapor deposition layer (Y) is 0.002 μm or more in thickness, the barrier properties against oxygen and water vapor tend to be improved. Also, when the inorganic vapor deposition layer (Y) is 0.5 μm or less in thickness, the barrier properties after bending tend to be better maintained.

[0031] (Overcoat layer (Z)) The overcoat layer (Z) contains a modified PVA (A). When the overcoat layer (Z) contains the modified PVA (A), the flex resistance tends to be improved. The modified PVA (A) has a vinyl alcohol unit (a) and a monomer unit (b) having a polar group. The monomer unit (b) does not contain a vinyl alcohol unit (a). The modified PVA (A) is not particularly limited as long as it has a vinyl alcohol unit (a) and a monomer unit (b), but it is preferable that it is not alkylene-modified.

[0032] The vinyl alcohol unit (a) is a unit represented by -CHCH(OH)-. The proportion of the vinyl alcohol unit (a) in all monomer units constituting the modified PVA (A) is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 75 mol% or more, and in some cases even more preferably 80 mol%, 85 mol%, 90 mol%, or 95 mol% or more.

[0033] The monomer unit (b) is a monomer unit other than the vinyl alcohol unit (a) and has a polar group. The polar group may be a monovalent group or a divalent or higher group. The polar group is not particularly limited, but from the viewpoint of further improving the flex resistance, it is preferable that the polar group is at least one selected from the group consisting of a carboxy group, an ester group (-COO-) and a silanol group. The polar group may be a group containing an ester group and represented by -COOR (R is a hydrocarbon group). The hydrocarbon group represented by R is preferably an alkyl group, more preferably an alkyl group having 1 to 3 carbon atoms. The silanol group refers to a group (Si-OH) in which a hydroxyl group (-OH) is bonded to a silicon atom.

[0034] The modified PVA (A) can be produced by a method such as copolymerization modification or post-modification, similar to the modified PVA that can be used for the above-mentioned substrate (X).

[0035] For example, the monomer unit (b) having a carboxyl group can be introduced into the modified PVA (A) by using an unsaturated acid such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, undecylenic acid, etc. as an unsaturated monomer. The monomer unit (b) having an ester group can be introduced into the modified PVA (A) by using an ester of an unsaturated acid, etc. as an unsaturated monomer, or by adjusting the degree of saponification. The monomer unit (c) having a silanol group can be introduced into the modified PVA (A) by using a compound having an unsaturated double bond and a trialkoxysilyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxy-ethoxy)silane, γ-methacryloxypropylmethoxysilane, etc. as an unsaturated monomer. At least a part of the trialkoxysilyl group becomes a silanol group upon saponification.

[0036] The proportion of the polar group-containing monomer units (b) in the total monomer units constituting the modified PVA (A) is preferably 0.05 mol % or more, more preferably 0.10 mol % or more, and preferably 30 mol % or less, more preferably 25 mol % or less.

[0037] When the modified PVA (A) has a monomer unit (b) containing a carboxy group as a polar group, the ratio of the monomer unit (b) containing a carboxy group in the total monomer units constituting the modified PVA (A) is preferably 0.05 mol% or more, more preferably 0.50 mol% or more. The ratio of the monomer unit (b) containing a carboxy group is preferably 10 mol% or less, more preferably 5 mol% or less. When the ratio of the monomer unit (b) containing a carboxy group is within the above range, the bending resistance tends to be more excellent.

[0038] When the modified PVA (A) has a monomer unit (b) containing an ester group as a polar group, the proportion of the monomer unit (b) containing an ester group in the total monomer units constituting the modified PVA (A) is preferably 5 mol% or more, more preferably 10 mol% or more. The proportion of the monomer unit (b) containing an ester group is preferably 30 mol% or less, more preferably 25 mol% or less. When the proportion of the monomer unit (b) containing an ester group is within the above range, the bending resistance tends to be more excellent.

[0039] When the modified PVA (A) has a monomer unit (b) containing a silanol group as a polar group, the proportion of the monomer unit (b) containing a silanol group in the total monomer units constituting the modified PVA (A) is preferably 0.05 mol% or more, more preferably 0.1 mol% or more. The proportion of the monomer unit (b) containing a silanol group is preferably 5 mol% or less, more preferably 2 mol% or less. When the proportion of the monomer unit (b) containing a silanol group is in the above range, the bending resistance tends to be more excellent.

[0040] The modified PVA (A) has a monomer unit (b) containing a carboxy group or a silanol group, and may further have a monomer unit (b) containing an ester group. In this case, the preferred ratio of the monomer unit (b) containing a carboxy group or a silanol group in the total monomer units constituting the modified PVA (A) is the same as the preferred ratio of the monomer unit (b) containing a carboxy group or a silanol group described above. On the other hand, in this case, the ratio of the monomer unit (b) containing an ester group in the total monomer units constituting the modified PVA (A) is preferably 0.1 mol% or more and 10 mol% or less, more preferably 0.3 mol% or more and 5 mol% or less, and even more preferably 1 mol% or more and 3 mol% or less. When the ratio of each monomer unit is within the above range, the bending resistance tends to be more excellent.

[0041] The total content of the vinyl alcohol units (a) and the monomer units (b) having a polar group in all the monomer units constituting the modified PVA (A) is preferably 95 mol % or more, more preferably 99 mol % or more, and in some cases may be even more preferably 99.9 mol % or more.

[0042] The viscosity average degree of polymerization of the modified PVA (A) is preferably 1000 to 4000, more preferably 1200 to 2600. When the viscosity average degree of polymerization of the modified PVA (A) is 1000 or more, the mechanical strength of the resulting vacuum packaging bag is improved, which is preferable. On the other hand, when the viscosity average degree of polymerization is 4000 or less, the film formability and the like are improved, which is preferable.

[0043] From the viewpoint of improving flex resistance, the content of the modified PVA (A) in the overcoat layer (Z) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may be 95% by mass or more. The overcoat layer (Z) may be substantially composed of the modified PVA (A) alone, or may be composed of only the modified PVA (A).

[0044] The overcoat layer (Z) may contain other components other than the modified PVA (A) within a range that does not impair the effects of the present invention. Examples of other components that can be contained in the overcoat layer (Z) include inorganic acid metal salts such as carbonates, hydrochlorides, nitrates, hydrogencarbonates, sulfates, hydrogensulfates, and borates, organic acid metal salts such as oxalates, acetates, tartrates, and stearates, metal complexes such as cyclopentadienyl metal complexes (e.g., titanocene) and cyano metal complexes (e.g., Prussian blue), layered clay compounds, crosslinking agents, polymer compounds other than the modified PVA (A), plasticizers, antioxidants, ultraviolet absorbers, and flame retardants. The content of the other components in the overcoat layer (Z) is preferably less than 50% by mass, more preferably less than 20% by mass, even more preferably less than 10% by mass, particularly preferably less than 5% by mass, and may be 0% by mass (no other components).

[0045] The thickness of the overcoat layer (Z) is 0.003 μm or more, preferably 0.02 μm or more, and more preferably 0.06 μm or more. The thickness of the overcoat layer (Z) is 5 μm or less, preferably 1 μm or less, more preferably 0.5 μm or less, even more preferably 0.2 μm or less, and particularly preferably 0.15 μm or less. If the thickness of the overcoat layer (Z) is outside the above range, the barrier properties after bending tend to decrease.

[0046] Regarding the overcoat layer (Z), the maximum intensity ratio (I(B) / I(C)) obtained by the following steps (1) to (3) MAX ) is preferably 1.20 or more. (1) At five arbitrarily selected points on the surface of the overcoat layer (Z), an analysis is performed in the depth direction (toward the inorganic deposition layer (Y)) by TOF-SIMS (time-of-flight secondary ion mass spectrometry). (2) For each detected fragment, calculate the average maximum fragment intensity (I(B)) at each measurement point, and the average intensity (I(C)) at the midpoint between the measurement start point (surface) and the measurement point of maximum intensity at each measurement point. The ratio of these is the intensity ratio (I(B) / I(C)). (3) The maximum intensity ratio (I(B) / I(C)) of each fragment is calculated. MAX )

[0047] TOF-SIMS is an analytical method in which an ion beam (primary ions) is irradiated onto a sample, and the emitted secondary ions (fragments) are acquired by the TOF (Time Of Flight) method and mass analyzed. In the analysis of the depth direction, sputtered ions are used, and the analysis of the depth direction can be performed while sputtering the multilayer structure. Therefore, in the analysis of the depth direction using TOF-SIMS, measurement points are obtained intermittently. "Five arbitrarily selected points" means five arbitrarily selected points on the surface of the overcoat layer (Z) of the multilayer structure, and the range analyzed at each measurement point is a range of 250 μm × 250 μm. Since the maximum intensity is measured at each of the five arbitrarily selected measurement points, the average value is I(B), and the average value of the intermediate measurement points between the measurement start point and the maximum intensity measurement point measured at each measurement point is I(C). For example, if the maximum intensity is obtained at the 11th measurement point, the 6th point is the intermediate measurement point, and if the maximum intensity is obtained at the 10th measurement point, the 5th and 6th measurement points are the intermediate measurement points. In addition, I(B) and I(C) are calculated for each fragment, and the intensity ratio (I(B) / I(C)) is also calculated for each fragment. The maximum intensity ratio (I(B) / I(C)) among the intensity ratios (I(B) / I(C)) for each fragment is defined as the maximum intensity ratio (I(B) / I(C)). MAX )

[0048] Maximum intensity ratio (I(B) / I(C) MAX ) can be used as an index of the degree of fragment distribution, and the maximum intensity ratio (I(B) / I(C) MAX ) is close to 1, it can be judged that the distribution is uniform, and (I(B) / I(C) MAX In the present invention, the maximum intensity ratio (I(B) / I(C)) is used as an index for confirming that polar groups are unevenly distributed at the interface between the overcoat layer (Z) and the inorganic vapor deposition layer (Y). MAX ) is used, and (I(B) / I(C) MAX When the intensity I(B) is 1.20 or more, the vicinity of the measurement point showing the maximum intensity I(B) is considered to be the interface between the overcoat layer (Z) and the inorganic vapor deposition layer (Y).

[0049] Maximum intensity ratio of the overcoat layer (Z) (I(B) / I(C) MAX The maximum intensity ratio (I(B) / I(C)) of the overcoat layer (Z) is preferably 1.20 or more, more preferably 1.40 or more, even more preferably 1.70 or more, and particularly preferably 2.00 or more. MAX When the maximum strength ratio (I(B) / I(C)) is equal to or greater than the lower limit, the polar groups in the overcoat layer (Z) tend to be localized at the interface with the inorganic vapor deposition layer (Y), and as a result, the flex resistance tends to improve. MAX ) may be 5.00 or less, 4.00 or less, or 3.00 or less.

[0050] The fragments of the overcoat layer (Z) observed by TOF-SIMS are not particularly limited, and examples thereof include silicon-based fragments such as SiO2, alcohol-based fragments such as C2H3O, C3H5O, etc. Specifically, the surface analysis of the overcoat layer (Z) in the depth direction using TOF-SIMS can be measured by the method described in the Examples.

[0051] (Method of manufacturing a multilayer structure) The method for producing the multilayer structure of the present invention is not particularly limited, and examples thereof include a production method including the steps of: (i) applying a coating liquid (S) containing a modified PVA (A) and a solvent onto an inorganic vapor deposition layer (Y) of a laminate having an inorganic vapor deposition layer (Y) on one surface of a substrate (X); and (ii) removing the solvent from the coating liquid (S) after application to form an overcoat layer (Z).

[0052] The laminate having the inorganic vapor deposition layer (Y) on one side of the substrate (X) used in step (i) can be prepared by the same method as the above-mentioned method for forming the inorganic vapor deposition layer (Y). A commercially available product can also be used as the laminate having the inorganic vapor deposition layer (Y) on one side of the substrate (X).

[0053] In the step (ii), a coating liquid (S) containing a modified PVA (A) and a solvent is applied onto the inorganic vapor deposition layer (Y).

[0054] The solvent used in the coating liquid (S) is not particularly limited, but is preferably water as the main component, and may be water alone. When water is used as the main component, other solvents to be used are preferably alcohols such as methanol, ethanol, and isopropanol.

[0055] The solid content concentration of the coating liquid (S) is preferably 0.01 to 15 mass%, more preferably 0.05 to 10 mass%, and even more preferably 0.1 to 5 mass%, from the viewpoints of the storage stability of the coating liquid (S), the coatability to the inorganic vapor deposition layer (Y), the degree of uneven distribution of polar groups in the resulting overcoat layer (Z), etc. The solid content concentration can be calculated, for example, by dividing the mass of the solid content remaining after distilling off the solvent from the coating liquid (S) by the mass of the coating liquid (S) subjected to the treatment.

[0056] The method for applying the coating liquid (S) is not particularly limited, and for example, known methods such as a casting method, a dipping method, a roll coating method, a gravure coating method, a screen printing method, a reverse coating method, a spray coating method, a kiss coating method, a die coating method, a metalling bar coating method, a coating method combined with a chamber doctor, a curtain coating method, and a bar coating method can be used.

[0057] The thickness of the layer (Z) formed after coating the coating liquid (S) on the inorganic vapor deposition layer (Y) can be controlled by the solid content concentration of the coating liquid (S) or the coating method. For example, in the case of the gravure coating method, the cell volume of the gravure roll can be changed.

[0058] In step (ii), the solvent in the coating liquid (S) applied onto the inorganic vapor deposition layer (Y) is removed to form an overcoat layer (Z) on the inorganic vapor deposition layer (Y). There is no particular limitation on the method for removing the solvent from the coating liquid (S) after application, and for example, a known drying method can be applied. Examples of the drying method include hot air drying, hot roll contact, infrared heating, and microwave heating. The drying temperature may be, for example, 80°C or more and 180°C or less, or 90°C or more and 150°C or less.

[0059] In addition, it is preferable to apply the coating liquid (S) on the inorganic vapor deposition layer (Y), leave it to stand, and then dry it. The time to stand after application until drying is, for example, 1 second or more, and preferably 2 seconds or more. The time to stand may be, for example, 1 minute or less. By leaving it to stand in this way, the polar group tends to be unevenly distributed near the interface with the inorganic vapor deposition layer (Y) in the overcoat layer (Z) to be formed. In order to promote the uneven distribution, it is also preferable to set the solid content concentration of the coating liquid (S) in a relatively low range. In this way, the fluid state of the coating liquid (S) on the inorganic vapor deposition layer (Y) is maintained for a long time, and the uneven distribution tends to be promoted.

[0060] (Other layers (J)) The multilayer structure of the present invention may include other layers (J) other than the substrate (X), inorganic vapor deposition layer (Y) and overcoat layer (Z) in order to improve various properties (e.g., heat sealability, barrier properties, mechanical properties, etc.). Such a multilayer structure of the present invention can be produced, for example, by adhering or forming another layer (J) directly or via an adhesive layer to a laminate including the substrate (X), inorganic vapor deposition layer (Y) and overcoat layer (Z). Examples of the other layer (J) include, but are not limited to, an ink layer, a polyolefin layer, a polyester layer, a polyamide layer, and a thermoplastic resin layer such as an ethylene-vinyl alcohol copolymer resin layer. An adhesive layer is also an example of the other layer (J). The multilayer structure of the present invention preferably includes at least two other layers (J), and more preferably includes the substrate (X), inorganic vapor deposition layer (Y) and overcoat layer (Z) between the at least two other layers (J).

[0061] The multilayer structure of the present invention may include an ink layer for printing a trade name or a pattern. The ink layer may be, for example, a film obtained by drying a liquid in which a polyurethane resin containing a pigment (e.g., titanium dioxide) is dispersed in a solvent, but may also be a film obtained by drying an ink containing a polyurethane resin not containing a pigment or other resin as a main component, or a resist for forming electronic circuit wiring. Examples of a method for applying the ink layer include gravure printing, as well as various application methods such as a wire bar, a spin coater, and a die coater. The thickness of the ink layer is preferably 0.5 μm or more and 10.0 μm or less, more preferably 1.0 μm or more and 4.0 μm or less.

[0062] By forming the outermost layer of the multilayer structure of the present invention as a polyolefin layer, it is possible to impart heat sealability to the multilayer structure and improve the mechanical properties of the multilayer structure. From the viewpoint of improving heat sealability and mechanical properties, the polyolefin is preferably polypropylene or polyethylene. In addition, in order to improve the mechanical properties of the multilayer structure, it is preferable to laminate at least one film selected from the group consisting of a film made of polyester, a film made of polyamide, and a film made of a hydroxyl group-containing polymer. From the viewpoint of improving the mechanical properties, the polyester is preferably polyethylene terephthalate (PET), the polyamide is preferably nylon-6, and the hydroxyl group-containing polymer is preferably an ethylene-vinyl alcohol copolymer.

[0063] The other layer (J) may be a layer formed by extrusion coating lamination. There is no particular limitation on the extrusion coating lamination method that can be used in the present invention, and any known method may be used. In a typical extrusion coating lamination method, a laminate film is produced by feeding a molten thermoplastic resin to a T-die and cooling the thermoplastic resin taken out from a flat slit of the T-die.

[0064] Examples of extrusion coat lamination methods other than the single lamination method include sandwich lamination and tandem lamination. The sandwich lamination method is a method in which a molten thermoplastic resin is extruded onto a first substrate, and a second substrate is supplied from a separate unwinder (unwinding machine) and bonded together to produce a laminate. The tandem lamination method is a method in which two single lamination machines are connected together to produce a five-layer laminate at once.

[0065] (Adhesive layer (H)) In the multilayer structure of the present invention, the inorganic vapor deposition layer (Y) may be laminated so as to be in direct contact with the substrate (X), or the inorganic vapor deposition layer (Y) may be laminated on the substrate (X) via an adhesive layer (H) disposed between the substrate (X) and the inorganic vapor deposition layer (Y). By interposing the adhesive layer (H), the adhesive strength between the substrate (X) and the inorganic vapor deposition layer (Y) may be increased. In addition, when laminating a layer (J) other than the adhesive layer (H), lamination via the adhesive layer (H) may increase the adhesive strength between the layers. As the adhesive constituting the adhesive layer (H), a two-liquid reactive polyurethane adhesive in which a polyisocyanate component and a polyol component are mixed and reacted is preferable. In addition, the adhesive strength may be further improved by adding a small amount of additives such as a known silane coupling agent. Suitable examples of the silane coupling agent include silane coupling agents having reactive groups such as an isocyanate group, an epoxy group, an amino group, a ureido group, and a mercapto group. By strongly bonding the substrate (X) and the inorganic vapor deposition layer (Y) via the adhesive layer (H), the bending resistance of the multilayer structure of the present invention can be further improved.

[0066] When an adhesive layer (H) is disposed between the substrate (X) and the inorganic vapor deposition layer (Y), the thickness of the adhesive layer (H) is preferably in the range of 0.03 μm to 0.18 μm. By setting the thickness of the adhesive layer (H) in this range, deterioration of the barrier property and appearance can be more effectively suppressed during the manufacture or processing of the vacuum packaging bag used in the vacuum insulator of the present invention, and further, the impact resistance of the vacuum insulator of the present invention can be improved. The thickness of the adhesive layer (H) is more preferably in the range of 0.04 μm to 0.14 μm, and even more preferably in the range of 0.05 μm to 0.10 μm.

[0067] The multilayer structure of the present invention had an oxygen permeability of 2.0 ml / (m2) measured according to JIS K7126 under conditions of 40°C, 0% RH (carrier gas side), and 90% RH (oxygen supply side) after three repeated reciprocating movements in a Gelboflex test according to ASTM F 392. 2 ·day·atm) or less is preferable, and 1.0 ml / (m 2 ·day·atm) or less is more preferable, and 0.5ml / (m 2 ·day·atm) or less is more preferable, and 0.40 ml / (m 2 Here, "40°C, 0% RH (carrier gas side), 90% RH (oxygen supply side)" means that at 40°C, the relative humidity on the carrier gas side is 90% RH and the relative humidity on the oxygen supply side is 0%, and "2.0 ml / (m 2 "·day·atm" means 1m of film 2 This indicates that 2.0 ml of oxygen permeates per day under a pressure difference of 1 atmosphere of oxygen gas.

[0068] (vacuum packaging bag) The multilayer structure of the present invention has excellent gas barrier properties after bending, and is therefore effective in suppressing deterioration of gas barrier properties in the production of vacuum packaging bags and the like. The vacuum packaging bag of the present invention comprises the multilayer structure of the present invention. The vacuum packaging bag is a packaging bag that is usually used with the inside reduced pressure, and comprises a film material containing the multilayer structure described above as a partition wall separating the inside from the outside. The vacuum packaging bag may comprise a plurality of the multilayer structures.

[0069] It is preferable that the surface layer of the vacuum packaging bag of the present invention is a polyolefin layer (hereinafter, sometimes abbreviated as PO layer) from the viewpoint of imparting heat sealability or improving mechanical properties. The polyolefin constituting such a polyolefin layer is preferably polypropylene or polyethylene. In addition, when emphasis is placed on further improving the mechanical properties of the vacuum packaging bag, it is preferable to laminate at least one film selected from the group consisting of a biaxially oriented polypropylene film, a polyester film, a polyamide film, and a PVA-based resin film as the other layer (J). From the viewpoint of improving the mechanical properties, polyethylene terephthalate (PET) is preferable as the polyester, nylon-6 is preferable as the polyamide, and ethylene-vinyl alcohol copolymer resin is preferable as the PVA-based resin.

[0070] The vacuum packaging bag of the present invention may have the following configuration, for example, from the outer layer to the inner layer of the vacuum insulator, where " / " means that the layers are laminated directly or via an adhesive layer, and " / / " means that the layers are laminated via an adhesive layer. (1) Overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / PO layer (2) Polyester layer / / overcoat layer (Z) / / inorganic vapor deposition layer (Y) / / substrate (X) / / PO layer (3) Polyester layer / / Base material (X) / Inorganic vapor deposition layer (Y) / Overcoat layer (Z) / / PO layer (4) Polyamide layer / / overcoat layer (Z) / / inorganic vapor deposition layer (Y) / / substrate (X) / / PO layer (5) Polyamide layer / / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (6) PO layer / / overcoat layer (Z) / / inorganic vapor deposition layer (Y) / / substrate (X) / / PO layer (7) Overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (8) Polyester layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (9) Polyamide layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (10) PO layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (11) Polyester layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (12) Polyamide layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (13) PO layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (14) Polyamide layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (15) PO layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / PO layer (16) Polyamide layer / / Polyester layer / Inorganic vapor deposition layer / / Overcoat layer (Z) / Inorganic vapor deposition layer (Y) / Substrate (X) / / PO layer (17) PO layer / / polyester layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (18) Polyamide layer / / polyester layer / / aluminum oxide vapor deposition layer / / overcoat layer (Z) / / inorganic vapor deposition layer (Y) / / substrate (X) / / PO layer (19) PO layer / / polyester layer / aluminum oxide vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (20) Polyamide layer / / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (21) PO layer / / substrate (X) / inorganic vapor deposition layer (Y) / overcoat layer (Z) / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (22) Nylon layer / inorganic vapor deposition layer / polyester layer / / inorganic vapor deposition layer / polyester layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (23) Polyester layer / / Nylon layer / / Overcoat layer (Z) / / Inorganic vapor deposition layer (Y) / / Substrate (X) / / PO layer (24) Nylon layer / / polyester layer / / overcoat layer (Z) / / inorganic vapor deposition layer (Y) / / substrate (X) / / PO layer (25) Polyester layer / polyester layer / inorganic vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer (26) Polyester layer / aluminum oxide vapor deposition layer / / polyester layer / aluminum oxide vapor deposition layer / / overcoat layer (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer

[0071] (Vacuum insulation) The vacuum insulator of the present invention comprises the vacuum packaging bag of the present invention and a core material disposed inside the vacuum packaging bag, and the inside is decompressed. Usually, in the vacuum insulator of the present invention, the space inside the vacuum packaging bag is in a vacuum state. The vacuum state here does not necessarily mean an absolute vacuum state, but indicates that the pressure of the space inside the vacuum packaging bag is sufficiently lower than atmospheric pressure. The pressure of the space inside the vacuum packaging bag is determined based on the required performance and ease of manufacture, and is usually 2 kPa (about 15 Torr) or less, preferably 200 Pa or less, more preferably 20 Pa or less, and even more preferably 2 Pa or less, from the viewpoint of exhibiting low thermal conductivity performance. The pressure of the space inside the vacuum packaging bag may be 0.001 Pa or more.

[0072] The core material used in the vacuum insulator of the present invention is not particularly limited as long as it has low thermal conductivity. For example, the core material may be perlite powder, silica powder, precipitated silica powder, diatomaceous earth, calcium silicate, glass wool, rock wool, and resin foam (e.g., styrene foam, urethane foam), etc. In addition, the core material may be a hollow container made of resin or inorganic material; a honeycomb structure, etc. If necessary, the core material may contain an adsorbent that adsorbs water vapor or gas, etc.

[0073] The thermal conductivity of the vacuum insulator of the present invention immediately after production is preferably 7.0 mW / (m·K) or less, more preferably 6.5 mW / (m·K) or less. On the other hand, the thermal conductivity immediately after production may be 1.0 mW / (m·K) or more. When the thermal conductivity is 7.0 mW / (m·K) or less, the low thermal conductivity performance of the vacuum insulator tends to be good. When the thermal conductivity is 1.0 mW / (m·K) or more, a vacuum insulator having good low thermal conductivity performance can be obtained at a relatively low cost. Here, the "thermal conductivity" is a value measured in accordance with JIS A 1412-1 (1999).

[0074] The vacuum insulator of the present invention has excellent bending resistance and therefore tends to have good thermal conductivity after bending at 90°. The thermal conductivity after bending at 90° is preferably 7.5 mW / (m·K) or less, more preferably 7.0 mW / (m·K) or less, and even more preferably 6.5 mW / (m·K) or less.

[0075] There are no particular limitations on the method for producing the vacuum insulator of the present invention, and any commonly used method can be used. For example, the following methods 1 to 3 can be used to produce a vacuum insulator of any shape and size depending on the intended use, etc. (Method 1) First, two sheets of multilayer structures having a rectangular shape in plan view, with a heat-sealable layer (e.g., a polyolefin layer) arranged on at least one surface, are prepared. The two multilayer structures are stacked with the heat-sealable layers facing inwards, and any three sides are heat-sealed to produce a packaging bag. Next, a core material is filled inside the packaging bag. Next, the space inside the packaging bag is evacuated, and the last side is heat-sealed in this state to obtain a vacuum insulator. (Method 2) First, a sheet of a multilayer structure having a rectangular shape in plan view is folded so that the layer having heat sealability is on the inside, and two arbitrary sides are heat-sealed to produce a packaging bag. Next, a core material is filled inside the packaging bag. Next, the space inside the packaging bag is evacuated, and the last side is heat-sealed in this state to obtain a vacuum insulator. (Method 3) First, a core material is sandwiched between two multilayer structures, or a multilayer structure is folded to sandwich the core material. Next, the peripheral portion where the multilayer structures overlap is heat-sealed, leaving a vacuum exhaust port, to produce a packaging bag with the core material disposed inside. Next, the internal space of the packaging bag is evacuated, and the vacuum exhaust port is heat-sealed in this state to obtain a vacuum insulator.

[0076] As described above, the vacuum insulator of the present invention is preferably obtained by heat-sealing the multilayer structure of the present invention. Since the multilayer structure of the present invention has an inorganic vapor deposition layer (Y), heat bridging (a phenomenon in which the aluminum foil transfers heat and the heat insulating performance is reduced) seen in vacuum insulators obtained from films having metal foil such as aluminum foil is unlikely to occur, and the vacuum insulator of the present invention tends to exhibit excellent heat insulating performance. From the viewpoint of suppressing this heat bridging, the vacuum insulator of the present invention may be a vacuum insulator obtained by heat-sealing the multilayer structure of the present invention and a film having metal foil. Examples of films having metal foil include films having layer structures such as polyamide layer / polyester layer / metal foil / PO layer, polyamide layer / metal foil / PO layer, and polyester layer / metal foil / PO layer.

[0077] The vacuum insulator of the present invention can be used for various applications requiring cold or hot insulation. In particular, the vacuum insulator is extremely unlikely to deteriorate in its low thermal conductivity over time even when used under high temperature or high humidity conditions, and has a sufficient service life as an insulating material, so it is useful for all thermal insulation applications requiring low thermal conductivity, such as tanks for water heaters, tanks for hot water toilets, tanks for vending machines, tanks for fuel cells, tanks for automobiles, thermal insulation bags for food, etc., for thermal insulation of PET bottles or cans, for thermal insulation of washing machine drums, servers for coffee and tea, etc., and jar pots. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the examples, " / " indicates that the two layers sandwiching " / " are directly laminated, and " / / " indicates that the two layers sandwiching " / / " are laminated via an adhesive. (Materials used in the Examples and Comparative Examples) VM-XL: "EVAL (registered trademark) VM-XL" manufactured by Kuraray Co., Ltd., aluminum-deposited biaxially stretched EVOH film (EVOH ethylene unit content 32 mol%, EVOH saponification degree 99.9 mol%, thickness 12 μm) VM-PET: Toray Industries, Inc.'s "VM-PET1510", aluminum-deposited PET film (thickness 12 μm) PET12: Toray Industries, Inc.'s "Lumirror (registered trademark) P60", PET film (thickness 12 μm) PE50: Idemitsu Unitech Co., Ltd. "Unilux (registered trademark) LS760C", LLDPE film (thickness 50 μm) Modified PVA (1): Polyvinyl alcohol with a viscosity average degree of polymerization of 1700, a degree of saponification of 98 mol%, and a silanol modification amount (the proportion of monomer units containing silanol groups (vinyl silane triol or units in which some of the hydroxyl groups of vinyl silane triol are alkoxy groups)) of 0.2 mol%. Modified PVA (2): Polyvinyl alcohol with a viscosity average degree of polymerization of 1700 and a degree of saponification of 78 mol% (ratio of monomer units (vinyl acetate units) containing ester groups: approximately 22 mol%) Modified PVA (3): Polyvinyl alcohol with a viscosity average degree of polymerization of 1800, a degree of saponification of 98 mol%, and an itaconic acid modification amount (the proportion of monomer units (vinyl itaconate units) containing a carboxyl group) of 1.0 mol%. PVA (1): Polyvinyl alcohol with a viscosity average polymerization degree of 1700 and a saponification degree of 100 mol% "Takelac (registered trademark) A520" (manufactured by Mitsui Chemicals, Inc., two-component polyurethane adhesive polyol component) "Takenate (registered trademark) A50" (Mitsui Chemicals, Inc., two-component polyurethane adhesive, isocyanate component)

[0079] (Evaluation method) (1) Thickness of the overcoat layer (Z) The multilayer structures obtained in the examples and comparative examples were cut with a microtome to prepare slices (thickness 0.3 μm) for cross-sectional observation. The prepared slices were fixed to a sample base with carbon tape and subjected to platinum ion sputtering at an acceleration voltage of 30 kV for 30 seconds. The cross-sections of the multilayer structures were observed with a field emission transmission electron microscope [apparatus: SU8000 manufactured by Hitachi High-Technologies Corporation], and the thickness of the overcoat layer (Z) was calculated. The measurement conditions were an acceleration voltage of 1 kV and a magnification of 20,000 times.

[0080] (2) Oxygen permeability after bending The multilayer structures obtained in the examples and comparative examples were cut into pieces of 20 cm x 25 cm, and a Gelbo flex test (bending test) was performed in accordance with ASTM F 392 using a Gelbo flex tester (BE-1005) manufactured by Tester Sangyo Co., Ltd. Specifically, the cut multilayer structures were conditioned at 23°C and 50% RH, and the conditioned multilayer structures were formed into cylindrical shapes with a diameter of 3.5 inches under the same atmosphere, and both ends were fixed to the Gelbo flex tester. The structures were subjected to three reciprocating motions with an initial interval of 7 inches, an interval at maximum bending of 1 inch, a twist of 440 degrees in the first 3.5 inches of the stroke, and a linear horizontal motion for the next 2.5 inches.

[0081] After bending, the multilayer structure was measured for oxygen permeability (unit: ml / (m) using MOCON OX-TRAN2 / 20 in accordance with JIS K7126. 2 The thermal conductivity (Tc) of the multilayer structure was measured. The multilayer structure was set with the deposition layer facing the oxygen supply side and the substrate facing the carrier gas side, and the oxygen supply side was at 40°C, 90% RH, and 1 atm, while the carrier gas side was at 40°C, 0% RH, and 1 atm. Nitrogen gas containing 2% by volume of hydrogen gas was used as the carrier gas. The oxygen permeability after bending was also evaluated based on the following evaluation criteria. A: More than 0.2 and less than 0.3 B: More than 0.3 and less than 0.4 C: More than 0.4 and less than 0.5 D: More than 0.5 but less than 0.6 E: more than 0.6 but less than 0.8 F: over 0.8 The above values ​​are in units of "ml / (m 2 ·day·atm).

[0082] (3) Thermal conductivity of vacuum insulation A vacuum insulator was produced using each of the multilayer structure (4-2) and the multilayer structures (C1-2) and (C2-2) obtained in Example 4 and Comparative Examples 1 and 2. Specifically, the multilayer structure was cut to 20 cm x 25 cm, and two sheets of each covering material were obtained. The two resulting covering materials were overlapped with the PE layers facing each other, and the three sides were heat-sealed with a width of 10 mm to produce a three-sided packaging bag. A small bag containing calcium oxide as a low thermal conductive core material and an adsorbent was filled from the opening of the resulting packaging bag, and the packaging bag was sealed at a temperature of 20°C and an internal pressure of 1.0 Pa using a vacuum insulation panel manufacturing device (KT-500RD model, manufactured by NPC Corporation) to produce a vacuum insulator. Glass fiber dried for 4 hours in an atmosphere at 160°C was used as the low thermal conductive core material. The obtained vacuum insulator was stored for a certain period of time at 23°C and 50% RH, and then the thermal conductivity (mW / (m·k)) of the vacuum insulator was measured using a thermal conductivity measuring device (Eko Seiki Co., Ltd., FOX314 model) with one side of the vacuum insulator at 38°C and the other side at 12°C. Measurements were performed on the vacuum insulator before bending and after bending it once vertically (90°).

[0083] (4) Maximum intensity ratio (I(B) / I(C) MAX ) Measurement For the multilayer structures obtained in the examples and comparative examples, a depth direction analysis of the overcoat layer surface was performed by TOF-SIMS under the following conditions using a "TOF-SIMS5" manufactured by ION-TOF. Five measurement points were randomly selected, and the average of the maximum intensity in each fragment was designated as I(B), and the average of the intensities at the measurement points midway between the measurement start point and the measurement point of the maximum intensity in each measurement point was designated as I(C). The intensity ratio (I(B) / I(C)) in each fragment was calculated. From the intensity ratios (I(B) / I(C)) in each fragment, the maximum intensity ratio (I(B) / I(C)) was calculated. MAX ) and its fragments were identified. <Measurement conditions> Primary ion source: Bi3 ++ Bu mode,0.2pA at 25 keV (10kHz) Charge compensation: Electron Flooding, No Oxygen Flooding Sputter ion source: Ar 1300+ ,2nA at 5KeV (100μsec) Measurement range: 500 x 500 μm (Sputtering) 250×250μm(128×128pix)Analysis,128scans Sequence: 2 flames analysis / 3 flames sputtering in 1 scan Analysis software: Surface Lab 6 (ION-TOF)

[0084] (Production Example 1) 2.5 g of modified PVA (1) was mixed with 47.5 g of distilled water, stirred at 90°C for 1 hour, and then cooled to room temperature to obtain a 5% by mass aqueous solution of PVA. Next, 24.0 g of the resulting aqueous PVA solution was mixed with 8.24 g of distilled water and 7.76 g of methanol, and stirred at room temperature for 30 minutes to prepare a coating solution (S-1).

[0085] (Production Examples 2 to 4) Coating solutions (S-2) to (S-4) were prepared in the same manner as in Production Example 1, except that modified PVA (2) (Production Example 2), modified PVA (3) (Production Example 3), or PVA (1) (Production Example 4) was used instead of modified PVA (1).

[0086] (Production Example 5) 3.42 parts by mass of tetramethoxysilane (TMOS) was dissolved in 4.1 parts by mass of methanol, followed by dissolving 0.68 parts by mass of γ-glycidoxypropyltrimethoxysilane, followed by adding 0.26 parts by mass of distilled water and 0.64 parts by mass of 0.1N (0.1 normal) hydrochloric acid to prepare a sol, which was stirred at 10°C for 1 hour to carry out hydrolysis and condensation reactions. The resulting sol was diluted with 9.25 parts by mass of distilled water, and then quickly added to 31.7 parts by mass of a 10% by mass aqueous solution of PVA (1) to prepare a coating liquid (S-5).

[0087] (Production Example 6) 2.5 g of modified PVA (1) was mixed with 47.5 g of distilled water, stirred at 90°C for 1 hour, and then cooled to room temperature to obtain a 5% by mass aqueous solution of PVA. Next, 8.0 g of the resulting aqueous PVA solution was mixed with 24.08 g of distilled water and 7.92 g of methanol, and stirred at room temperature for 30 minutes to prepare a coating solution (S-6).

[0088] (Production Example 7) 6.0 g of modified PVA (1) was mixed with 44.0 g of distilled water, stirred at 90°C for 1 hour, and then cooled to room temperature to obtain a 12% by mass aqueous solution of PVA. Next, 30.0 g of the resulting aqueous PVA solution was mixed with 2.72 g of distilled water and 7.28 g of methanol, and stirred at room temperature for 30 minutes to prepare a coating solution (S-7).

[0089] Example 1 The coating liquid (S-1) was applied to the aluminum vapor deposition surface of "VM-XL" using a bar coater so that the thickness after drying would be 30 nm, and then the coating was left to stand for 3 seconds. It was then dried at 100°C for 3 minutes to produce a multilayer structure (1-1) in which the overcoat layer (Z) / aluminum vapor deposition layer / biaxially stretched EVOH layer were laminated in this order. The overcoat layer (Z) of the resulting three-layer multilayer structure (1-1) was evaluated for the maximum strength ratio (I(B) / I(C)) according to the method described in the above evaluation method (4). MAX The results are shown in Table 1.

[0090] A two-component adhesive ("Takelac A-520" and "Takenate A-50") was applied to one side of each of "PET12" and "PE50", and laminated to form a structure of PET12 / adhesive layer / overcoat layer (Z) / aluminum vapor deposition layer / biaxially oriented EVOH layer / adhesive layer / PE50 to produce a multilayer structure (1-2). The thickness of the overcoat layer (Z) and the oxygen permeability after bending of the resulting seven-layer multilayer structure (1-2) were measured according to the methods (1) and (2) above. The results are shown in Table 1.

[0091] (Examples 2 to 11, Comparative Examples 1 to 8) Except for changing the layer structure (deposition film), the type of coating solution, the standing time after coating, and the thickness of the overcoat layer (Z) as shown in Table 1, the multilayer structures (2-1) to (11-1) of the three-layer structure and the multilayer structures (2-2) to (11-2) of the seven-layer structure of the three-layer structure and the multilayer structures (C1-1) to (C8-1) of the seven-layer structure and the multilayer structures (C1-2) to (C8-2) of the seven-layer structure of the three-layer structure and the multilayer structures (C1-2) to (C8-2) of the seven-layer structure of the three-layer structure and the multilayer structures (C1-2) to (C8-2) of the seven-layer structure of the three-layer structure and the multilayer structures (C1-2) to (C8-2) of the three-layer structure and the multilayer structures (C1-2) to (C8-2) of the three-layer structure and the multilayer structures (C1-2) to (C1-2) of the seven-layer structure of the three-layer structure and the multilayer structures (C1-2) to (C1-2) ...

[0092] [Table 1]

[0093] [Table 2]

[0094] (Examples 12 to 15) Three-layer multilayer structures (12-1) to (15-1) and seven-layer multilayer structures (12-2) to (15-2) of Examples 12 to 15 were produced in the same manner as in Example 1, except that the type of coating liquid, the standing time after coating, and the thickness of the overcoat layer (Z) were changed as shown in Table 3. The thickness of the overcoat layer (Z) and the oxygen permeability after bending of the obtained multilayer structures (12-2) to (15-2) were measured according to the above methods (1) and (2). The results are shown in Table 3.

[0095] [Table 3]

[0096] From Examples 1 to 6, it can be seen that when modified PVA (A) is used, good flex resistance is shown, and among them, Example 3, in which the thickness of the overcoat layer is 0.09 μm, is remarkably excellent in flex resistance. Also, from Examples 4 to 6, 12 to 15, it can be seen that when modified PVA having a silanol group, an ester group, or a carboxy group is used, good flex resistance is shown. When the overcoat layer (Z) is not provided as in Comparative Example 1, the flex resistance is poor, and when non-modified PVA is used as in Comparative Examples 2 to 4, the flex resistance is also poor. Furthermore, when a PET film is used as the substrate instead of a PVA-based resin film as in Comparative Examples 5 and 6, the gas barrier property is significantly reduced, and even when a coating liquid in which PVA and a silane compound are mixed is used as in Comparative Examples 7 and 8, the flex resistance is insufficient.

[0097] From the comparison of Examples 4, 7, and 8, when the solid concentration of the coating liquid for forming the overcoat layer (Z) is different, the maximum intensity ratio (I(B) / I(C)) of TOF-SIMS is MAX From this result, it can be seen that when the solid content is moderate as in Example 4, specific polar groups (groups from which SiO2 fragments are derived in Example 4) tend to be unevenly distributed at the interface of the inorganic vapor deposition layer (Y), resulting in improved flex resistance.

[0098] From the comparison of Examples 4, 9 to 11, it was found that the maximum intensity ratio (I(B) / I(C)) also changed depending on the time the sample was left to stand after coating with the coating liquid. MAX As in Example 4, after coating the coating liquid (S-1) with a bar coater, waiting for 3 seconds before drying showed good bending resistance.

[0099] FIG. 1 shows the maximum intensity ratio (I(B) / I(C)) of the measurement results of the depth profile analysis using TOF-SIMS in Example 4. MAX1 is a graph showing one of the measurement results in which the fragment is SiO2. In the graph of FIG. 1, the X-axis (horizontal axis) is Dose density (a parameter in the depth direction, the larger the value, the deeper the measurement point), and the Y-axis (vertical axis) is Intensity (the intensity of the fragment of SiO2, the larger the value, the greater the amount). From this graph, it can be seen that the intensity of SiO2 is increased in the interface region between the overcoat layer (Z) and the inorganic vapor deposition layer (Y), and it can be said that the results suggest that silanol groups are unevenly distributed at the interface. Although it is not certain, in Example 4 and the like, the interaction between the silanol groups and aluminum, which is a component of the inorganic vapor deposition layer (Y), causes the silanol groups to be unevenly distributed at the interface, and the overcoat layer (Z) and the inorganic vapor deposition layer (Y) are firmly attached to each other, suppressing the occurrence of defects in the inorganic vapor deposition film due to bending, and as a result, it is thought that the deterioration of the barrier property due to bending is suppressed.

Claims

1. A substrate (X), an inorganic vapor deposition layer (Y), and an overcoat layer (Z) are provided in this order; The substrate (X) is made of a biaxially stretched polyvinyl alcohol-based resin film, the overcoat layer (Z) contains a modified polyvinyl alcohol (A) having a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the vinyl alcohol unit (a); The thickness of the overcoat layer (Z) is 0.003 μm or more and 1 μm or less, the proportion of the monomer units (b) having a polar group in all monomer units constituting the modified polyvinyl alcohol (A) is 0.05 mol % or more and 30 mol % or less; A multilayer structure, wherein the content of the modified polyvinyl alcohol (A) in the overcoat layer (Z) is 70% by mass or more.

2. 2. The multilayer structure according to claim 1, wherein the polar group is at least one selected from the group consisting of a carboxy group, an ester group, and a silanol group.

3. The maximum intensity ratio (I(B) / I(C)) obtained by the following steps (1) to (3) MAX 3. The multilayer structure according to claim 1, wherein the saturation coefficient (S) is 1.20 or more. (1) At five arbitrarily selected points on the surface of the overcoat layer (Z), a depth direction analysis is performed by TOF-SIMS. (2) For each detected fragment, the average value of the maximum fragment intensity at each measurement point (I(B)) and the average value of the intensity at the measurement point midway between the measurement start point and the measurement point of maximum intensity at each measurement point (I(C)) are calculated, and the ratio of these values ​​is defined as the intensity ratio (I(B) / I(C)). (3) The maximum intensity ratio (I(B) / I(C)) among the obtained intensity ratios for each fragment is called the maximum intensity ratio (I(B) / I(C)). MAX )

4. The multilayer structure according to any one of claims 1 to 3, further comprising a layer (J) other than the substrate (X), the inorganic vapor deposition layer (Y), and the overcoat layer (Z).

5. The multilayer structure according to claim 4, comprising at least two other layers (J), and comprising a substrate (X), an inorganic vapor deposition layer (Y) and an overcoat layer (Z) between the at least two other layers (J).

6. The multilayer structure according to any one of claims 1 to 5, wherein the biaxially stretched polyvinyl alcohol-based resin film is a biaxially stretched film containing as a main component an ethylene-vinyl alcohol copolymer having an ethylene unit content of 10 mol% or more and 65 mol% or less and a saponification degree of 90 mol% or more.

7. In the Gelbo Freck test according to ASTM F 392, after three repeated reciprocating movements, the oxygen transmission rate measured according to JIS K7126 under conditions of 40°C, 0% RH (carrier gas side) and 90% RH (oxygen supply side) was 2.0 ml / (m 2 The multilayer structure according to any one of claims 1 to 6, wherein the viscosity is 100 / sq.m. / day atm or less.

8. A vacuum packaging bag comprising the multilayer structure according to any one of claims 1 to 7.

9. A vacuum insulator comprising the vacuum packaging bag according to claim 8 and a core material disposed inside the vacuum packaging bag, the inside of the vacuum packaging bag being reduced in pressure.

Citation Information

Patent Citations

  • Gas barrier film, gas barrier laminate and method for producing the same

    JP2008056861A

  • Vacuum heat insulation material

    JP2008114520A

  • Packing material for vacuum heat insulation material, vacuum heat insulation material, and article with vacuum heat insulation material

    JP2019002442A

  • Gas barrier laminated film

    JP2019064074A

  • Multilayer structure and product including the same

    JP2019104161A